A longitudinal study of the changes in BMI, waist circumference, waist-to-height-ratio and desired BMI of the participants in the 4th, 5th and 6th survey of the Tromsø Study. - Aars, Nils Abel (UiT Norges arktiske universitet, 2014)
Background: prevalence of obesity and overweight continues to increase in Norway, and more in young than old. This thesis has sought to describe the changes in BMI, with supplementary analyses of WC and WHtR, over a 13-year period. Furthermore, desired BMI (DBMI) has been analysed to assess whether the discrepancy between weight and desired weight is dependent on BMI categories of normal weight, overweight or obese. Methods and materials: The thesis has used data from the Tromsø Study, specifically surveys 4 (T4), 5 (T5) and 6 (T6). The material has been analysed both cross-sectionally and longitudinally, and so the population available for analyses depends upon participation in the different surveys. Results: The results show that BMI increased over the 13-year study period in both genders and all age groups but those aged 70-74 in T4. Increase was significantly associated with age at baseline, with a negative trend of BMI-increase with increasing age. A similar pattern applies for WC and WHtR. DBMI increased in all age groups of both genders, but the increase of DBMI was less than that of BMI during the period. Conclusion: Between T4 and T6, BMI increased in all age groups of both genders, an increase which is also evident in WC and WHtR. The analyses of BMI from the longitudinal cohort of T4, T5 and T6 indicate that the best part of the increase occurred between T4 and T5. The difference between BMI and DBMI is different between BMI categories, with normal weight people expressing low discrepancy between BMI and DBMI. The results confirm and extend previous knowledge on development of BMI in the Norwegian population.